KUALITAS LAYANAN RUMAH SAKIT DI ERA JKN: PERAN KEPESERTAAN, AKSESIBILITAS, DAN PEMBIAYAAN SEBAGAI FAKTOR PENENTU - Abghi Hafizhan Shulan; Artanti Puspita; Fatih Hilal Athaya; Ilham Yoga Pangestu; Fitri Amalia (STKIP Subang, 2025)
Although JKN coverage reached 98.45% in 2024, the quality of hospital services for JKN participants remains low (average satisfaction of 68%), accompanied by major complaints regarding responsiveness and empathy, recurring BPJS deficits, and unequal geographical access. This study aims to examine the effect of JKN membership, healthcare accessibility, and financing on the quality of hospital services through the SERVQUAL model. A quantitative explanatory research approach with a cross-sectional design was applied to 120 active JKN participants selected through purposive sampling. Multiple linear regression analysis using IBM SPSS 27 showed that all three variables had a positive and significant effect, both partially and simultaneously (F = 13.376; p < 0.001; R² = 0.257). Financing was the strongest predictor (β = 0.365), followed by accessibility (β = 0.257) and JKN membership (β = 0.198). Reforms in contributions, acceleration of claims, strengthening of telemedicine, and intensification of PBPU membership socialization are recommended to support quality UHC in 2029.